Diagnostic interval of inflammatory bowel disease in Chinese children and its relationship with growth parameters: a retrospective study - Zhou, Juan; Chen, BinRong; Wang, ZhiCheng; Liu, Li; OuYang, HongJuan; Luo, YanHong; Zhang, WenTing; Liu, ChenXi; Zhan, MeiZheng; Duan, JiaQi; Li, CanLin; Jiang, Na; et al. (Frontiers in Pediatrics, 2025)
BackgroundDelayed diagnosis of inflammatory bowel disease (IBD) is common in Europe and North America, with limited research in Asia. We aimed to investigate factors influencing delayed diagnosis of IBD in Chinese children and the impact of delayed diagnosis on growth.MethodsThis was a retrospective study. Clinical data on children with IBD were collected through electronic medical records. The diagnostic interval includes the time from symptom onset to hospital admission and admission to diagnosis. Diagnostic delay was defined as the upper quartile of the time interval from the first symptom to the diagnosis of IBD. For the effect on growth indicators, the length of follow-up was at least 3 months from diagnosis.ResultsThis study included 222 children with IBD, predominantly with Crohn's disease (86.0%). Approximately one-quarter of children require more than 366 days to be diagnosed with IBD, primarily due to the extended interval between the onset of initial symptoms and hospital admission. Multivariate logistic regression models showed that fever was associated with a prolonged time interval from first symptom onset to admission and the odds ratio (OR) was 0.45 [95% confidence interval (CI) 0.22–0.94]. Age and bloody stools were associated with prolonged intervals from admission to diagnosis, with ORs of 0.84 (95% CI 0.77–0.92) and 0.36 (95% CI 0.14–0.94), respectively. Delayed diagnosis was associated with height at first admission and follow-up. Children with a delayed diagnosis had a 5.87-fold higher chance of growth retardation upon initial admission compared to children without a delayed diagnosis (95% CI 1.59–24.05). After 15.7 months of follow-up, this elevated risk remained (OR 3.28, 95% CI 1.00–10.50).ConclusionDelayed diagnosis is common in Chinese children with IBD and is associated with persistent height impairment.